2006
DOI: 10.1590/s1679-87592006000300005
|View full text |Cite
|
Sign up to set email alerts
|

Colony size-frequency distributions among different populations of the scleractinan coral Siderastrea stellata in Southwestern Atlantic: implications for life history patterns

Abstract: A B S T R A C TColony size-frequency distributions of reef corals may be used to infer growth potential and population responses upon environmental changes. The present paper compares the size structure of colonies of Siderastrea stellata Verrill, 1868, among 11 sites, six of them distributed along a gradient of sediment deposition in Abrolhos, Bahia, Brazil (18 o S). Results indicated that the population structure is likely to be influenced by local conditions, rather than large scale factors, such as latitud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Assessing size structures of coral populations can provide information about important ecological processes such as coral survivorship, recruitment, fecundity, mortality and community responses to various stress events such as mass coral bleaching or Acanthaster plancii outbreaks (Meesters et al, 2001;McClanahan et al, 2008). Records of coral size class distributions and frequencies can provide an in-depth understanding of trends in the condition and resilience of reef ecosystems, rather than the data offered from more simplified metrics such as coral cover or diversity (Bak and Meesters, 1998;de Barros and Pires, 2006;Meesters et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Assessing size structures of coral populations can provide information about important ecological processes such as coral survivorship, recruitment, fecundity, mortality and community responses to various stress events such as mass coral bleaching or Acanthaster plancii outbreaks (Meesters et al, 2001;McClanahan et al, 2008). Records of coral size class distributions and frequencies can provide an in-depth understanding of trends in the condition and resilience of reef ecosystems, rather than the data offered from more simplified metrics such as coral cover or diversity (Bak and Meesters, 1998;de Barros and Pires, 2006;Meesters et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Weedy corals with a shared life history strategy may compete with each other in disturbed environments [56]. Large colony size is typical of stress-tolerant species, with a greater reserve of polyps from which to draw energy, often increasing the resilience of these colonies to changes over time [57].…”
Section: Discussionmentioning
confidence: 99%
“…Oigman-Pszczol and Creed (2011) suggested that the large number of smalldiameter colonies is an adaptive reproductive strategy developed in reefs subject to environmental stress. Another important factor is that this species tends to reproduce early and incubate larva (Barros and Pires 2006). This phenomenon may be the consequence of a survival strategy under turbid conditions, temperature anomalies, and resuspension of sediments, all of which were present in our study site, which was characterized by high mortality rates and short life spans (Soares et al 2017).…”
Section: Coral Resilience and Contributing Factorsmentioning
confidence: 91%